Study of Waves Propagating in Anisotropic Homogeneous Microstretch Elastic Medium - Rani, Neetu; Garg, Savita (Communications in Mathematics and Applications, 2023)
The present study deals with the plane waves moving in a solid medium qualifying for anisotropic, homogeneous, microstretch and elastic properties. Primarily, the Christoffel equations have been derived for propagation of waves (coupled longitudinal and coupled transverse) in the medium. A system of homogeneous equations has been established to study polarization of medium particles for wave motion, polarization of medium particles in microrotation and microstretch present in the medium. Condition of solvability for a system of homogeneous linear equations has been applied to derive an equation for determining phase velocities of coupled waves propagating in the medium. Using the software Mathematica and hypothetical values for parameters and elastic constants, numerical discussion has been carried out to see the possible number of waves propagating in arbitrarily chosen phase directions in the medium. Finally, a special case of anisotropic homogeneous elastic medium (absence of microstretch) has been discussed to support the results derived in the present study.
Keywords: Microstretch; Microrotation; Phase velocity; Polarization; Coupled longitudinal waves; Coupled transverse waves